Peran Search Engine Terhadap keputusan Pemesanan Hotel di Masa Pandemi Covid-19 - parlagutan silitonga; Lalu Aswadi Jaya; Sigit Dani Nugroho (LPPM and Travel Operation Department Universitas Asa Indonesia, 2022)
This study aims to analyze the role of brand image, service quality and Reputation Performance Score in determining hotel bookings in Jakarta during the pandemic. The study population covered all guests who stayed at the research object with purposive sampling techniques. While the applied analysis method is descriptive. The results of the study explained that online booking is dominated by online travel agents. The implications of this research are that managers will intensify treating and updating information to online travel entrepreneurs.